High-strength stable aluminum-lithium alloy and preparation method thereof
By adding Sn/Sc/Si elements to aluminum-lithium alloys and combining it with conventional T6 treatment, the problem of performance degradation of aluminum-lithium alloys at high temperatures has been solved, resulting in improved strength and thermal stability, reduced material costs, and simplified manufacturing processes. This makes it suitable for high-temperature structural components in the aerospace field.
Patent Information
- Application Number
- CN202610283870.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-03-10
- Publication Date
- 2026-08-25
- Estimated Expiration
- 2046-03-10
AI Technical Summary
Existing aluminum-lithium alloys exhibit rapid performance degradation at high temperatures, making it difficult to meet the service requirements of critical components in supersonic aircraft. Furthermore, the application of traditional pre-deformation processes in large structural components is limited.
Sn/Sc/Si elements were added to the third-generation Al-Cu-Li alloy to optimize the microalloying element content. Sn elements captured vacancies and segregated them at the T1 phase interface, which suppressed the coarsening rate. Combined with conventional T6 treatment, a precipitate phase with high strength and good thermal stability was formed.
Without relying on pre-deformation processes, aluminum-lithium alloys maintain high strength at high temperatures, reducing material costs and simplifying the manufacturing process, making them suitable for large integral structural components.
Smart Images

Figure CN121802251B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of metal materials technology, and in particular to a high-strength and stable aluminum-lithium alloy and its preparation method. Background Technology
[0002] With the increasing demands for energy conservation, emission reduction, and lightweight equipment, the research and development of lightweight structural materials is becoming increasingly important. Among them, aluminum-lithium alloys, due to their high specific strength, low density, and excellent specific stiffness, are widely used in the aerospace field and are considered one of the most promising lightweight high-strength structural materials. Third-generation aluminum-lithium alloys have been widely used in the forward, mid-, and aft fuselage sections of aircraft, as well as structural components such as floor beams, seat rails, boundary beams, and cabin floors, with service temperatures below 150°C. This is attributed to the insufficient performance stability of the alloy at high temperatures (above 180°C): coarsening or even dissolution of the T1 phase leads to rapid performance degradation of the alloy at high temperatures. Furthermore, critical components such as the fuselage skin, tail fins, and load-bearing frames near the engines of supersonic aircraft place even more stringent requirements on the service performance of materials at 250°C. Developing high-strength and stable aluminum-lithium alloys is of great significance for further promoting the lightweighting of aerospace equipment.
[0003] The design of high-strength and stable aluminum alloys is mainly based on the following mechanisms: first, by controlling the alloy composition and interface structure, the coarsening rate of the original strengthening phase at high temperatures is suppressed; second, by adding transition metals and rare earth elements, a large number of high-melting-point dispersed phases are precipitated in the aluminum matrix. Compared with traditional Al-Cu alloys, the research and development of high-strength and stable aluminum-lithium alloys is in its early stages. Existing work mainly focuses on using Zr, Sc, Ti, and rare earth elements to form L12-structured nanoscale dispersed particles to improve the thermal stability of strengthening phases such as T1. In addition, large integrated structural components are often difficult to pre-deform, and the traditional strategy of relying on pre-strain to promote precipitation strengthening is significantly constrained in engineering applications. Therefore, research on composition design and microstructure control of aluminum-lithium alloys that can achieve high strength and high thermal stability without pre-deformation conditions has important scientific significance and engineering value.
[0004] Based on this, the present invention designs a low-cost, high-strength, stable aluminum-lithium alloy and its preparation method. Summary of the Invention
[0005] This invention provides a high-strength and stable aluminum-lithium alloy and its preparation method, the purpose of which is to solve the above-mentioned problems existing in the background art.
[0006] To achieve the above objectives, embodiments of the present invention provide a high-strength and stable aluminum-lithium alloy and its preparation method. This invention adds one or more Sn / Sc / Si elements to a third-generation Al-Cu-Li alloy, with Sn being essential. The content of existing microalloying elements in the alloy is optimized, enabling the alloy to achieve performance equivalent to or even superior to traditional T8 alloys in the T6 state. Furthermore, the synergistic effect of trace elements is fully utilized to improve the morphology and interface of precipitates, resulting in thinner precipitates after thermal exposure. This promotes precipitate formation while suppressing their coarsening rate. For example, Sn segregates at the T1 phase interface, reducing the coarsening rate of the precipitates, leading to stronger T6 state performance and better thermal stability, significantly improving the strength and thermal stability of the aluminum-lithium alloy. In addition, this invention partially replaces the expensive Ag element with Sn, significantly reducing raw material costs while ensuring the overall performance of the alloy.
[0007] One aspect of the present invention provides a high-strength, stable aluminum-lithium alloy comprising, by mass fraction: Cu 4%~6%, Li 0.8%~2%, Ag 0.01%~0.8%, Mg 0.2%~0.8%, Zn 0.2%~0.8%, Sn 0.01%~0.3%, Sc 0~0.3%, Si 0~0.5%, Ti 0.01%~0.3%, Mn 0.01%~0.3%, Zr 0.01%~0.3%, with the balance being Al and impurity elements; wherein the impurity elements are less than or equal to 0.1%; and the total of Sn, Sc, and Si is <0.5%.
[0008] Preferably, the high-strength stable aluminum-lithium alloy comprises the following components by mass fraction: Cu 4%~6%, Li 0.8%~2%, Ag 0.01%~0.3%, Mg 0.2%~0.8%, Zn 0.2%~0.8%, Sn 0.1%~0.3%, Sc 0~0.3%, Si 0~0.5%, Ti 0.01%~0.3%, Mn 0.01%~0.3%, Zr 0.01%~0.3%, with the balance being Al and impurity elements; wherein, the impurity elements are less than or equal to 0.1%; and the total of Sn, Sc, and Si is <0.5%.
[0009] Preferably, the high-strength stable aluminum-lithium alloy comprises the following components by mass fraction: Cu 4%~6%, Li 0.8%~2%, Ag 0.15%~0.3%, Mg 0.2%~0.8%, Zn 0.2%~0.8%, Sn 0.1%~0.3%, Sc 0~0.3%, Si 0~0.5%, Ti 0.01%~0.3%, Mn 0.01%~0.3%, Zr 0.01%~0.3%, with the balance being Al and impurity elements; wherein, the impurity elements are less than or equal to 0.1%; and the total of Sn, Sc, and Si is <0.5%.
[0010] Another aspect of the present invention provides a method for preparing the above-mentioned high-strength and stable aluminum-lithium alloy, comprising the following steps:
[0011] The metal components are mixed according to the specified high-strength stable aluminum-lithium alloy composition ratio, smelted and cast into ingots, then homogenized and air-cooled to room temperature, then hot-deformed and air-cooled to room temperature, followed by solution treatment, quenching treatment, natural aging and artificial aging treatment to obtain the high-strength stable aluminum-lithium alloy.
[0012] Preferably, the homogenization treatment is performed at a temperature greater than or equal to 400°C, and the holding time is from 10 minutes to 48 hours.
[0013] Preferably, the temperature of the heat deformation treatment is greater than or equal to 400°C, and the heat holding time is 10 minutes to 24 hours.
[0014] Preferably, the solution treatment temperature is greater than or equal to 400°C, and the holding time is from 10 minutes to 24 hours.
[0015] Preferably, the quenching treatment includes one or more of water quenching, oil quenching, and gas quenching.
[0016] Preferably, the aging process includes at least one of natural aging process and artificial aging process.
[0017] Preferably, the natural aging process takes between 10 minutes and 240 hours.
[0018] Preferably, the temperature of the artificial aging treatment is 80°C to 240°C, and the aging time is 10 minutes to 96 hours.
[0019] Reaction principle:
[0020] This invention enhances the strength and thermal stability of aluminum-lithium alloys by synergistically regulating vacancies, precipitation behavior, and interface stabilization mechanisms. The strength of aluminum-lithium alloys primarily derives from the precipitation of nano-reinforcing phases such as T1, whose nucleation and growth processes are highly dependent on the number and distribution of residual vacancies after quenching. This invention introduces trace amounts of Sn, utilizing the high binding energy between Sn and vacancies to effectively capture and stabilize vacancies after quenching, forming a stable solute-vacancy complex. This significantly improves the diffusion kinetics during the artificial aging stage, accelerating the nucleation of the T1 phase and increasing its number density. Simultaneously, Sn segregation at the T1 / matrix interface forms an interface layer, reducing interface energy and suppressing the coarsening process of the T1 phase at high temperatures. Sc segregation in the θ′ phase also inhibits coarsening, thereby improving the stability of various reinforcing phases. This invention achieves strength equivalent to or even superior to the traditional T8 state using only conventional T6 treatment without relying on pre-deformation. Furthermore, the addition of Sn reduces the material cost associated with Ag, ultimately resulting in a low-cost, simple-process, high-strength, stable aluminum-lithium alloy.
[0021] The above-described solution of the present invention has the following beneficial effects:
[0022] 1. This invention uses trace amounts of Sn to partially replace expensive Ag, thereby reducing the cost of alloy raw materials while ensuring the overall performance of the alloy through equivalent or better strengthening and stabilizing mechanisms.
[0023] 2. The Sn element added in this invention has a high binding energy with vacancies, which can efficiently capture and stabilize vacancies after quenching, promote the formation of solute-vacancy complexes and early clusters, thereby accelerating the precipitation rate of strengthening phases such as T1 and increasing their number density, so that the alloy can obtain high strength without relying on complex pre-deformation processes.
[0024] 3. This invention introduces Sn elements to cause segregation at the T1 phase / matrix interface, thereby reducing the interfacial energy and suppressing the coarsening rate of the T1 phase under medium and high temperature conditions, significantly improving the stability of the strengthening phase and slowing down the strength decay of the alloy during long-term service.
[0025] 4. The alloy of the present invention can achieve or exceed the strength level that is traditionally obtained in the T8 state (tensile or pre-deformation + artificial aging) under the conventional T6 state. No additional pre-deformation process is required, which simplifies the heat treatment and forming process, reduces the manufacturing difficulty and process cost, and is conducive to the engineering promotion and application in large integral structural parts and complex components. Attached Figure Description
[0026] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0027] Figure 1 This is a process flow diagram for preparing a high-strength and stable aluminum-lithium alloy according to the present invention;
[0028] Figure 2 The figures show the hardness change curves of aluminum-lithium alloys during artificial aging and thermal exposure processes in Examples 1, 3, and 6 and Comparative Examples 1 and 2 of this invention; wherein, Figure 2 (a) shows the hardness change curves of aluminum-lithium alloys in Examples 1, 3, 6 and Comparative Examples 1, 2 during the artificial aging process at 180°C. Figure 2 (b) Hardness change curves of aluminum-lithium alloys in Examples 1, 3, 6 and Comparative Examples 1, 2 during long-term heat exposure at 200°C;
[0029] Figure 3 These are microscopic images of the aluminum-lithium alloys prepared in Example 1 and Comparative Example 1 of this invention after artificial aging and thermal exposure; wherein, Figure 3 (a) and (b) are microscopic images of the aluminum-lithium alloy prepared in Comparative Example 1 after artificial aging at 180℃ for 10 h and heat exposure at 200℃ for 48 h, respectively. Figure 3 (c) and 3(d) are microscopic images of the aluminum-lithium alloy prepared in Example 1 after artificial aging at 180°C for 10 h and heat exposure at 200°C for 48 h, respectively;
[0030] Figure 4 The images shown are microscopic images of the T1 phase, EDS surface scans, and line scans of the Sn element in the aluminum-lithium alloy prepared in Example 1 of this invention, respectively, from
[110] . Al and
[112] Al Directional observation; among them, Figure 4 (a) and 4(d) are HAADF-STEM images of the T1 phase (5nm and 20nm). Figure 4 (b) and 4(e) are EDS surface scans of Sn element (5nm and 20nm). Figure 4 (c) and 4(f) are respectively Figure 4 EDS line scans of Sn elements near phase T1 in (a) and 4(d). Detailed Implementation
[0031] To make the technical problems, technical solutions and advantages of the present invention clearer, a detailed description will be given below in conjunction with the accompanying drawings and specific embodiments.
[0032] Unless otherwise defined, all technical terms used herein have the same meaning as commonly understood by those skilled in the art. The technical terms used herein are for the purpose of describing particular embodiments only and are not intended to limit the scope of the invention.
[0033] Unless otherwise specified, all raw materials, reagents, instruments and equipment used in this invention can be purchased from the market or prepared by existing methods.
[0034] This invention addresses the existing problems by providing a high-strength, stable aluminum-lithium alloy and its preparation method. This invention has the following beneficial effects:
[0035] 1. This invention uses trace amounts of Sn to partially replace expensive Ag, thereby reducing the cost of alloy raw materials while ensuring the overall performance of the alloy through equivalent or better strengthening and stabilizing mechanisms.
[0036] 2. The Sn element added in this invention has a high binding energy with vacancies, which can efficiently capture and stabilize vacancies after quenching, promote the formation of solute-vacancy complexes and early clusters, thereby accelerating the precipitation rate of strengthening phases such as T1 and increasing their number density, so that the alloy can obtain high strength without relying on complex pre-deformation processes.
[0037] 3. This invention introduces Sn elements to cause segregation at the T1 phase / matrix interface, thereby reducing the interfacial energy and suppressing the coarsening rate of the T1 phase under medium and high temperature conditions, significantly improving the stability of the strengthening phase and slowing down the strength decay of the alloy during long-term service.
[0038] 4. The alloy of the present invention can achieve or exceed the strength level that is traditionally obtained in the T8 state (tensile or pre-deformation + artificial aging) under the conventional T6 state. No additional pre-deformation process is required, which simplifies the heat treatment and forming process, reduces the manufacturing difficulty and process cost, and is conducive to the engineering promotion and application in large integral structural parts and complex components.
[0039] The following description is provided through specific embodiments and comparative examples.
[0040] Example 1
[0041] This embodiment provides a high-strength and stable aluminum-lithium alloy, comprising the following components by mass percentage: Cu 4.2%, Li 1.1%, Ag 0.3%, Mg 0.4%, Zn 0.3%, Sn 0.1%, Ti 0.1%, Mn 0.3%, Zr 0.1%, with the balance being Al and unavoidable impurity elements;
[0042] The specific process for preparing the above-mentioned high-strength and stable aluminum-lithium alloy is as follows: Figure 1 As shown, it includes the following steps:
[0043] The metal components are mixed according to the specified high-strength stable aluminum-lithium alloy composition ratio, smelted and cast into ingots, then homogenized in an air-circulating resistance furnace at 500°C for 24 hours, and then air-cooled to room temperature. Next, the ingots are hot-rolled to 2 mm at 460°C with a reduction of 20% per pass, and then air-cooled to room temperature. Finally, the ingots are solution-treated at 530°C, water-quenched, naturally aged for 7 days, and artificially aged at 180°C for 10 hours to obtain the high-strength stable aluminum-lithium alloy.
[0044] Example 2
[0045] The difference from Example 1 is that the high-strength stable aluminum-lithium alloy component Sn is 0.2%, while all other components are the same as in Example 1.
[0046] Example 3
[0047] The difference from Example 1 is that the high-strength stable aluminum-lithium alloy component Ag is 0.15%, while all other components are the same as in Example 1.
[0048] Example 4
[0049] The difference from Example 1 is that the high-strength stable aluminum-lithium alloy composition also includes 0.2% Si, while the rest are the same as in Example 1.
[0050] Example 5
[0051] The difference from Example 1 is that the high-strength stable aluminum-lithium alloy composition also includes 0.1% Sc, while the rest are the same as in Example 1.
[0052] Example 6
[0053] The difference from Example 1 is that the high-strength stable aluminum-lithium alloy composition also includes 0.1% Sc and 0.2% Si, while the rest are the same as in Example 1.
[0054] Comparative Example 1
[0055] The difference from Example 1 is that the high-strength stable aluminum-lithium alloy composition does not include 0.1% Sn, while all other components are the same as in Example 1.
[0056] Comparative Example 2
[0057] The difference from Example 1 is that the high-strength stable aluminum-lithium alloy composition does not include Sn 0.1%, and in the preparation process, a room temperature pre-deformation treatment is included before artificial aging treatment, with a pre-deformation amount of 3.5%. All other aspects are the same as in Example 1.
[0058] Comparative Example 3
[0059] The difference from Example 1 is that Sn 0.1% in the high-strength stable aluminum-lithium alloy component is replaced with Sc 0.1%, while all other aspects are the same as in Example 1.
[0060] Comparative Example 4
[0061] The difference from Example 1 is that Sn 0.1% in the high-strength stable aluminum-lithium alloy composition is replaced with Si 0.2%, while all other aspects are the same as in Example 1.
[0062] Comparative Example 5
[0063] The difference from Example 1 is that Sn 0.1% in the high-strength stable aluminum-lithium alloy composition is replaced with Sc 0.1% and Si 0.2%, while all other components are the same as in Example 1.
[0064] Comparative Example 6
[0065] The difference from Example 1 is that Sn 0.1% in the high-strength stable aluminum-lithium alloy composition is replaced with Sn 0.2%, Sc 0.2%, and Si 0.2%, while all other components are the same as in Example 1.
[0066] Performance testing
[0067] The aluminum-lithium alloys of Examples 1-6 and Comparative Examples 1-6 were subjected to hardness tracking and quasi-static tensile tests under artificial aging and heat exposure, respectively, including the following steps:
[0068] Alloy hardness testing was conducted on a Vickers hardness tester. The test load was uniformly 9.8 N, the indenter was a square pyramidal diamond indenter with a relative angle of 136°, and the holding time was 10 s. The hardness was determined by measuring the diagonal length of the indentation.
[0069] Quasi-static uniaxial tensile testing was performed using a 100kN MTS Landmark testing machine at a speed of 2mm / min.
[0070] To obtain the average hardness value of the sample, at least 5 points were measured for each sample and the average value was taken.
[0071] Figure 2 The figures show the hardness changes of the aluminum-lithium alloys in Examples 1, 3, and 6, and Comparative Examples 1 and 2, during artificial aging at 180°C and heat exposure at 200°C. The peak hardness of Example 1 is comparable to that of Comparative Example 2; the aluminum-lithium alloy with trace amounts of Sn achieves the T8 state performance of traditional aluminum-lithium alloys without pre-deformation treatment. The peak hardness of Example 3 is comparable to that of Comparative Example 1; adding Sn to an alloy with reduced Ag content achieves the performance of alloys with normal Ag content. The aluminum-lithium alloys in these examples exhibit slower hardness decay during heat exposure at 200°C, demonstrating superior thermal stability.
[0072] Figure 3 These are microscopic images of the aluminum-lithium alloys in Example 1 and Comparative Example 1 after artificial aging at 180°C for 10 hours and heat exposure at 200°C for 48 hours. Quantitative statistics show that the alloy in Example 1 has a higher density of precipitated phases at the aging peak, and the average thickness of the T1 phase is also thinner after heat exposure at 200°C for 48 hours. The coarsening rate of the precipitated phases during long-term heat exposure is slower than that in Comparative Example 1.
[0073] Figure 4 This is a segregation diagram of Sn elements at the T1 / matrix interface of the aluminum-lithium alloy in Example 1 after heat exposure at 200°C for 48 hours. Figure 4 It can be seen that Sn elements can segregate at the T1 phase interface, suppressing the coarsening of the precipitated phase.
[0074] To ensure data repeatability, the aluminum-lithium alloys of Examples 1-6 and Comparative Examples 1-6 were subjected to at least three tensile tests. The quasi-static tensile test results are shown in Table 1.
[0075] Table 1
[0076]
[0077] Table 1 shows the yield strength, tensile strength, and elongation of the aluminum-lithium alloys in Examples 1-6 and Comparative Examples 1-6 after artificial aging and heat exposure. As shown in Table 1, compared to Example 3 and Comparative Example 1 (T6), replacing Ag with Sn still achieves the peak performance of aluminum-lithium alloys with normal Ag content, and its thermal stability is superior. This means that by partially replacing expensive Ag with trace amounts of Sn, the cost of alloy raw materials is reduced while ensuring the overall performance of the alloy through equivalent or superior strengthening and stabilizing mechanisms. Comparing Examples 1 and 2 with Comparative Examples 1 (T6) and 2 (T8), because Sn atoms have a high binding energy with quenching vacancies in the Al matrix, Sn atoms can preferentially capture and stabilize these supersaturated vacancies after solution quenching, suppressing the rapid annihilation of vacancies in the early stages of natural or artificial aging. The vacancies stabilized by Sn further act as diffusion carriers, promoting the formation of early precursors such as Cu / Li-rich atomic clusters. This lowers the nucleation energy barrier of the T1 phase while providing more nucleation sites, promoting T1 phase nucleation and increasing its number density. During thermal exposure, Sn can segregate at the T1 phase interface, reducing the interfacial energy of the T1 / Al matrix and inhibiting T1 phase coarsening. Therefore, the alloys prepared in Examples 1 and 2 can achieve the performance of conventional aluminum-lithium alloys in the T8 state without relying on complex pre-deformation processes, and their thermal stability is superior. This preparation process does not require additional pre-deformation steps, simplifying the heat treatment and forming process, reducing manufacturing difficulty and process costs, and is conducive to engineering applications in large integral structural parts and complex components. In Example 6, the thermal stability is optimal under the combined effect of Sn, Sc, and Si elements because Sc / Si elements can achieve the optimal thermal stability at θ. / Interfacial segregation stability of Al matrix θ This further improves the thermal stability of the alloy. In summary, the aluminum-lithium alloys in Examples 1-6 still exhibit good performance after prolonged heat exposure at 200°C, indicating that they have good thermal stability.
[0078] Compared to Example 1, Comparative Examples 1 and 2 exhibited poorer thermal stability because no additional microalloying elements were added to stabilize the T1 phase. Compared to Example 1, Comparative Examples 3, 4, and 5 also showed poorer thermal stability because the added Sc / Si elements could not segregate at the interface of the T1 / Al matrix, thus failing to suppress the coarsening rate of the main strengthening phase. Compared to Example 1, Comparative Example 6 exhibited poor strength and thermal stability because the excessive Sn / Sc elements added easily precipitated coarse phases such as W during early heat treatment, consuming some solute atoms such as Cu, Sn, and Sc.
[0079] The above description represents the preferred embodiments of the present invention. It should be noted that those skilled in the art can make various improvements and modifications without departing from the principles of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A high-strength and stable aluminum-lithium alloy, characterized in that, The composition, by mass fraction, includes the following components: Cu 4%~6%, Li 0.8%~2%, Ag 0.01%~0.8%, Mg 0.2%~0.8%, Zn 0.2%~0.8%, Sn 0.01%~0.3%, Sc 0~0.3%, Si 0~0.5%, Ti 0.01%~0.3%, Mn 0.01%~0.3%, Zr 0.01%~0.3%, with the balance being Al and impurity elements; wherein, the impurity elements are less than or equal to 0.1%; and the total of Sn, Sc, and Si is <0.5%.
2. The high-strength, stable aluminum-lithium alloy according to claim 1, characterized in that, The Sn content is 0.1% to 0.3% by mass fraction.
3. The high-strength, stable aluminum-lithium alloy according to claim 1, characterized in that, The content of Ag is 0.01% to 0.3% by mass fraction.
4. The high-strength, stable aluminum-lithium alloy according to claim 3, characterized in that, The content of Ag is 0.15% to 0.3% by mass fraction.
5. A method for preparing a high-strength, stable aluminum-lithium alloy as described in any one of claims 1 to 4, characterized in that, Includes the following steps: The metal components are mixed according to the specified high-strength stable aluminum-lithium alloy composition ratio, smelted and cast into ingots, then homogenized and air-cooled to room temperature, then hot-deformed and air-cooled to room temperature, followed by solution treatment, quenching treatment, natural aging and artificial aging treatment to obtain the high-strength stable aluminum-lithium alloy.
6. The method for preparing high-strength stable aluminum-lithium alloy according to claim 5, characterized in that, The homogenization treatment is carried out at a temperature greater than or equal to 400°C, and the holding time is from 10 minutes to 48 hours.
7. The method for preparing high-strength stable aluminum-lithium alloy according to claim 5, characterized in that, The heat distortion treatment temperature is greater than or equal to 400℃, and the heat holding time is from 10 minutes to 24 hours.
8. The method for preparing high-strength, stable aluminum-lithium alloy according to claim 5, characterized in that, The solution treatment temperature is greater than or equal to 400°C, and the holding time is from 10 minutes to 24 hours; the quenching treatment includes one or more of water quenching, oil quenching, and gas quenching.
9. The method for preparing high-strength stable aluminum-lithium alloy according to claim 5, characterized in that, The natural aging process takes from 10 minutes to 240 hours.
10. The method for preparing the high-strength stable aluminum-lithium alloy according to claim 5, characterized in that, The temperature for the artificial aging process is 80°C to 240°C, and the aging time is 10 minutes to 96 hours.
Citation Information
Patent Citations
High-strength heat-resistant aluminum alloy and application thereof
CN115537617A
High-strength heat-resistant aluminum-lithium alloy and preparation method thereof
CN117107133A